Nonreductive Physicalism and Mental Causation - Amen, Miguel (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2006)
In this work I articulate and defend a problem about the place of the mind in the causation of behaviour. Ask why someone did a certain action and you can see the problem arise, if only you assume certain plausible suppositions about the world. The suppositions are taken to be those of nonreductive materialism. I think that the argument from exclusion, originally developed by Jaegwon Kim, shows that unless there is overdetermination, the mental cannot be causally relevant in the causation of behaviour. It is my view, however, that a proper understanding of overdetermination shows that the overdetermination move is not available to the nonreductive physicalist. That is, he cannot escape exclusion by claiming that the mental overdetermines the physical in the causation of our actions. It is argued that neither appeals to economy nor to Bennett's counterfactual test are good ways to decide matters of overdetermination. That should be decided in terms of the ability of a theory to consistently permit such overdetermination, which however is shown not to be the case for nonreductive materialism. Moreover, in general all realized properties will face this problem - assuming them to be causally relevant will ignite exclusionary claims and in the competition for relevance, physical properties will have a better and more fundamental claim for relevance, threatening once again to relegate realized properties to the category of epiphenomena.